Engineering Innovative Ways To Sustain Learning For Pre-Service Economic And Management Science Teachers In Curriculum Practice - Mphuthi, Mochina; Tshelane, Molaodi (My University, 2022)
Remote learning is the future of teaching and learning. The inception of Covid 19 has disrupted the traditional face to face teaching and learning and raised a need for scholars to investigate innovative ways to adapt to global disruption. Remote learning was the preferred option as it is effective and efficient to sustain learning even post the disruptions. In recent years, extensive research has been conducted on how to use the industrial revolution in curriculum reform. Remote learning is one of the recent initiatives in the curriculum and pedagogy reform package in South Africa that involves the use of remote learning to improve teaching and learning. This article investigates innovative ways to engineer a shift to remote learning for pre-service economic and management science teachers and the use of remote learning curriculum practice to achieve pedagogy mastery. The aim of the article is to answer the research question: what innovative ideas can be generated to engineer shift to remote learning in curriculum practice. Architecture theory is used as the main lens for the study. Connectivism learning approach as a form of education science is used to generate data in this study. Connectivism is immersed in the narrative that knowledge is distributed across networks through connections and connectivity, and learning is guided by connections and connectedness. Based on technology, connectivism is a learning approach that emphasizes knowledge acquisition focused on the future, rather than the past. Connectivism is relevant to this study because it encourages and changes the essential nature of building knowledge. Connectivism empowers teacher educators as well as preservice students through using collaboration in learning. Critical discourse analysis was used to arrive at the following broad findings: Pre-service economic and management science teachers should participate in diverse learning spaces indicated by the varying standards of learning embodied in the existing context of the South African society embracing educational inequalities. Implementation of the three c`s of remote learning: connectivity, content and capacity will enhance possibilities for economic and management sciences pre-service teachers to use remote learning in their practice of the curriculum. The paper concludes with expected recommendations that the prefigured remote learning for professional teaching practices be reconfigured.
Keywords: Remote learning; Engineering; Connectivism; Curriculum practice; Architecture theory